Synthesis of Zinc Oxide (ZnO) from Used Battery Waste as An Antibacterial Agent on Cotton Fabric - Aryati, Nadya Putri; Fiadillah, Maulidia Fara; Lalus, Jelita Marista; Rahayu, Cindi Aulia; Rifa'i, Fitra Ahmad; Widiarti, Nuni (Chemistry Department, The University of Brawijaya, 2025)
One of the heavy metals found in the metal coating industry waste is Zn, which can be used as a precursor to produce ZnO compounds. This study used the coprecipitation method to synthesize ZnO from used battery waste as an antibacterial agent for cotton fabric and cellulose fiber materials. The synthesized ZnO was characterized by its functional groups using FTIR, its crystal structure and size using XRD, and its surface morphology using SEM. The results of FTIR characterization were carried out at wave numbers of 400 - 4000 cm-1 and verified the presence of ZnO groups at wave numbers of 439 cm-1 and 442 cm-1. XRD characterization showed a hexagonal structure with a Zincite phase, and the crystallite sizes of X and Y batteries were 9.52 nm and 8.79 nm, respectively, with a composition consisting of 100% Zincite. SEM characterization of ZnO from X batteries at 1000x and 5000x magnifications showed more homogeneous particle sizes than Y batteries. The diameters of the inhibition zone on each ZnO synthesized from Y and X batteries were 11.8 mm and 9.7 mm, indicating moderate inhibition against S. aureus bacteria. The diameters of the inhibition zone on the cotton fabric samples coated with ZnO from Y and X batteries were 3.5 mm and 2.7 mm, respectively, indicating low inhibition against S. aureus bacteria. No inhibition zone was observed for the synthesized ZnO and the fabric samples coated with ZnO from Y and X batteries when tested against E. coli bacteria.